2020
DOI: 10.1073/pnas.1905730117
|View full text |Cite
|
Sign up to set email alerts
|

Pressure sensing through Piezo channels controls whether cells migrate with blebs or pseudopods

Abstract: Blebs and pseudopods can both power cell migration, with blebs often favored in tissues, where cells encounter increased mechanical resistance. To investigate how migrating cells detect and respond to mechanical forces, we used a “cell squasher” to apply uniaxial pressure to Dictyostelium cells chemotaxing under soft agarose. As little as 100 Pa causes a rapid (<10 s), sustained shift to movement with blebs rather than pseudopods. Cells are flattened under load and lose volume; the actin cytoskeleton is reo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 67 publications
8
66
0
Order By: Relevance
“…Different microfluidic systems were recently designed to determine the impact of confinement on single [21][22][23][24] and collective 25,26 cell migration, nucleus deformation, [27][28][29][30][31][32] rupture and repair 33,34 and cell division. 35,36 Using such systems, a switch from a mesenchymal to an amoeboid mode of migration upon cell confinement was highlighted for various mesenchymal cell types 37 including embryonic progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Different microfluidic systems were recently designed to determine the impact of confinement on single [21][22][23][24] and collective 25,26 cell migration, nucleus deformation, [27][28][29][30][31][32] rupture and repair 33,34 and cell division. 35,36 Using such systems, a switch from a mesenchymal to an amoeboid mode of migration upon cell confinement was highlighted for various mesenchymal cell types 37 including embryonic progenitor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Srivastava et al identified Piezo in Dictyostelium cells as a pressure sensor, required for a Ca 2+ -dependent switch from pseudopod to bleb-based migration 49 . We similarly observed that compressing cells beyond the point of initial contact with the pillar resulted in elevated cytosolic Ca 2+ and induced blebbing.…”
Section: Similarly Changes In Actomyosin Contractility and Substramentioning
confidence: 99%
“…Moreover, mechanisms of motility vary even among amoebozoans. For example, while E. histolytica blebs (Maugis et al, 2010), D. discoideum can switch between blebbing and using actin-filled pseudopods for α-motility (Srivastava et al, 2020;Tyson et al, 2014;Zatulovskiy et al, 2014). Therefore, empirically determining the mechanisms that control phenotypes like motility and phagocytosis in an understudied organism is an important step toward understanding its cell biology.…”
Section: Introductionmentioning
confidence: 99%